Simply electrifying : the technology that transformed the world, from Benjamin Franklin to Elon Musk - Roach, Craig (BenBella Books, Inc., 2017)
Looks at the stories of the researchers, innovators, businesspeople, and regulators who shaped how electricity was understood and used, from early researchers like Benjamin Franklin to contemporary innovators like Elon Musk.